E-047 Coil embolization in recurred cerebral aneurysm previously undergone surgical clipping. (22nd July 2018) - Kim, S; Jin, S; Park, J; Jeong, Y; Baek, J; Jeong, H
Abstract : Object: Surgical revision of recurrent cerebral aneurysms is technically difficult. Therefore, an alternative treatment option, coil embolization, has been utilized in these cases. The aim of this study was to evaluate the clinical and angiographic outcomes of coil embolization in patients with recurred cerebral aneurysms after microsurgical clipping. Methods: Between May 1999 and February 2016, 19 patients (4 men and 15 women) with 19 recurrent aneurysms who previously underwent surgical clipping were treated by coil embolization. Results: Nine patients presented with subarachnoid hemorrhage (SAH) (47.4%). The interval between surgical clipping and coil embolization was 143.5±66.1 months with a range of 43 to 276 months. Immediate radiological findings after coil embolization showed complete occlusion in 10 cases, a residual neck in 8 cases, and a residual sac in one case. Procedure-related thromboembolic complications associated with permanent morbidity occurred in one case. The mean clinical follow-up period was 58.3±38.8 months. Poor clinical outcomes (modified Rankin scale score ≥3) at the end of clinical follow-up were reported in 5 patients (26.3%). Angiographic follow-up was available for 12 patients (63.2%). Major recurrence was detected in 5 patients (41.7%), and a tendency of aneurysm re-growth rather than coil compaction was noted in all cases. Conclusion: In our series, coil embolization for recurrent aneurysms after surgical clipping was feasible but had a high recurrence rate. Recurrence of cerebral aneurysms had a tendency to result in aneurysm re-growth rather than coil compaction. Disclosures: S. Kim: None. S. Jin: None. J. Park: None. Y. Jeong: None. J. Baek: None. H. Jeong: None.